Faktor-Faktor yang Mempengaruhi Motivasi Kerja Karyawan pada PT. Nyonya Meneer - Hastuti, Wahyu; Tirtono, Tjandra (Jurnal Ilmiah Aset, 2013)
This study aimed to determine the factors that influence employee motivation at PT. Nyonya Meneer Semarang. Its population was all employees at PT. Nyonya Meneer Semarang, amounting to 375 employees, while the samples were taken 79 employees. The sampling technique used was conveniene sampling. The data analysis technique used was multiple linear regression analysis. The results showed that based on partial hypothesis, internal factors influenced employee motivation, seen from significantvalue 0.005 <0.05. While external factors didn’t influence employee motivation,seen from significant value 0.083> 0.05. The Simultaneous hypothesisshowed that both internaland external factors influenced employee motivation.